Biomimetic, Programmable, and Part‐by‐Part Maneuverable Single‐Body Shape‐Morphing Film. (21st December 2022) - Jeong, Yongrok; Ahn, Junseong; Ha, Ji-Hwan; Ko, Jiwoo; Hwang, Soon-Hyoung; Jeon, Sohee; Bok, Munjeong; Jeong, Jun-Ho; Park, Inkyu
Abstract : Recently, shape‐morphing films (SMFs) have been actively researched due to their diverse applications such as soft robotics, soft grippers, and healthcare/wearable devices. Their complex movements are typically made by assembling multiple actuation elements in a single system. However, the unreliability during the assembly process is a critical issue, which has restricted their practical usage. In order to resolve this problem, herein, a biomimetic, programmable, and part‐by‐part maneuverable single‐body SMF is proposed. Programming of the SMF adopts a similar mechanism to Bauhinia variegates, whereby nonequivalent volume changes due to external stimuli cause the bending of the overall film. The patterned elastic modulus of the SU‐8 microwall prescribes the preferred bending direction. Part‐by‐part maneuvering is accomplished by controlling the voltage distribution of the underlying electrothermal heater. The fabricated single‐body SMF demonstrates the complex movements of the inchworm (pose stabilization: front‐to‐back flip and back‐to‐front flip; basic movements: crawl, left turn, and right turn) and Drosera Capensis (insect gripping via hierarchical morphology). The proposed method for the fabrication of a biomimetic, programmable, and part‐by‐part maneuverable single‐body SMF can successfully replace the conventional assembly process and achieve advanced SMF technology by enabling various complex movements toward practical applications. Abstract : Herein, the issues maintained in the assembly process of the soft robots by unifying them in a single part‐by‐part programmable and maneuverable system hinted from the biomimetic structure are solved. In conclusion, the suggested system is successfully fabricated and mimicks the complex motion of artificial inchworm and artificial Drosera Capensis .